Exploring Athlete Personal Branding: An Analysis of Audience Reception of Instagram Ads - Mardyan Widjaja; Altobeli Lobodally (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study aims to analyze the interpretation of the Sepbol football Community about the personal branding of an athlete in Lay's Chip Cam Instagram ads. Personal branding is an interesting strategy for ad creators in promoting a product. Although the products advertised are often contradictory to the brand ambassador chosen. Like athletes that used to promote unhealthy foods. This study uses the theory of encoding-Decoding Stuart Hall, with the method of audience reception analysis and in-depth interviews as data collection techniques. The study found that the four community members who were informants in the study were in two different positions. Four people are in a hegemonic-dominant position, yet one person is in a negotiating position. The informant is in a negotiating position because his arguments regarding the use of athletes as brand ambassadors have a different dichotomy of functions.